The Association Between Obesity, Depression, and Anxiety: Evidence From a Community Health Needs Assessment Survey - Grace Adams; Angela Murcia (Georgia Southern University, 2016)
Background: The obesity epidemic has garnered much attention as a public health crisis. In order to make progress, it is necessary to understand the factors associated with obesity. One area of research needing more development is the link between obesity and other chronic health conditions. The objective of the present study was to further understand the relationship between obesity and the prevalence of anxiety and depression in Athens-Clarke County in northeast Georgia. Methods: Data from the 2015 Athens-Clarke County Community Health Needs Assessment (n=1234) were used to assess the relationship between obesity and the prevalence of anxiety and depression among households at the county level. A linear probability model was utilized to estimate the effects of anxiety and depression, separately on the prevalence of household obesity. Household demographic and economic characteristics were applied as controls. Results:The presence of anxiety in a household was associated with a 16% increase in the probability of obesity in the household (p Conclusions: The results show a positive and statistically significant association between mental health and obesity. Although these findings are specific to Athens-Clarke County residents, the results are similar to those for national surveys, which find an association between obesity and mental health outcomes. Recommendations for public health organizations include the need for additional research and evaluation to create programs that address underlying issues pertaining to obesity.